Experiential versus attitudinal topic types and task performance in EFL monologues - Assiri, Mohammed Shuaib (Universitas Pendidikan Indonesia, 2019)
With the aim of contributing to the existing ‎literature on the relationships between task ‎and topic facets, discourse features, topic ‎familiarity, and task performance in speaking, this study used EFL monologues to examine how two different sets of ‎topics―experiences/preferences versus opinions/attitudes―relate to task performance. The ‎task performance was measured using discourse features, including how language ‎elicited was complex, fluent, and lexically diverse. The study also explores how discourse ‎features themselves relate to one another across the two sets of topics. The data for the study ‎came from monologues performed by 63 adult EFL learners at the intermediate level of an ‎intensive English program in Saudi Arabia. The learners produced the monologues in response ‎to two summative tests (i.e., Test 1: experiences preferences and Test 2: opinions ‎attitudes). Using parametric statistical analyses (incl., the paired samples T-test and the ‎Pearson correlation), it was found that while experiences and preferences evoked more fluent ‎language than did opinions and attitudes, the latter elicited more complex and lexically ‎diverse language. Also, a significant, positive correlation existed between fluency and complexity for experiences and preferences, whereas lexical diversity was significantly positively correlated with complexity for opinions and attitudes. The study report concludes ‎with practical implications for enhancing task performance of monologues in the areas of ‎complexity, fluency, and lexical diversity.‎